Фетальна анатомічна мінливість довгих гілок плечового сплетення - Коваль, О. А.; Хмара, Т. В. (Вісник медичних і біологічних досліджень, 2022)
Summary. Information about the anatomical variability of the roots, trunks, bundles, and branches of the brachial plexus is of important practical importance for understanding the mechanisms of injuries to the shoulder, forearm, and hand. Knowledge of the variant anatomy of the brachial plexus in people of different ages is necessary for successful operations, effective analgesia, as well as for the interpretation of clinical symptoms in the practice of neurologists. The aim of the study – to establish the anatomical variability of the musculocutaneous, ulnar, median, and radial nerves in human fetuses of different ages. Materials and Methods. The study was conducted on preparations of the upper limbs of 28 human fetuses of 81.0–310.0 mm parietal-coccygeal length (PCL) using macromicroscopic dissection and morphometry. Results. During anatomical dissection of the upper limbs of 28 human fetuses aged 4–8 months, variants of the fetal topography of bundles and nerves of the subclavian part of the brachial plexus were found in three cases of 170.0 mm, 245.0 mm, 250.0 mm PCL. In fetuses with 170.0 mm and 245.0 mm PCL, connections between the median and ulnar nerves in the form of connecting branches were observed, and the median nerve began with one root from the medial bundle of the subclavian part of the brachial plexus. In a fetus with 250.0 mm PCL, an atypical variant of topography was established for nerves of the lateral and medial bundles of the subclavian part of the brachial plexus, and a doubling of the ulnar nerve was also detected. Conclusions. Double innervation of some shoulder and forearm muscles was found in some human fetuses. The established variants of the topography and connections of the median, ulnar, and musculocutaneous nerves in human fetuses are determined by the peculiarities of the structural organization and multifunctionality of the muscles of the shoulder and forearm, the patterns of their complex prenatal development, the available sources of blood supply, and other factors. The described variants of the fetal anatomy of the long branches of the brachial plexus should be considered not only by theoreticians, but also by clinicians, primarily neurologists, orthopedists, and surgeons.